‘Āʼisha Bint al-Shāṭi’s Thoughts on Tarāduf and Their Implications for the Istinbāṭ of Law - Imran, Maizul; Ismail, Ismail (Al-Risalah, 2019)
As a book containing miracles, in literature, the miracles of the Quran have been proven by ʻĀʼisha Bint al-Shāṭiʼ through her theory i‘jāz lughawī. She showed the importance of the correct method of interpretation of the Qurʼan from aspects of tarāduf (synonym). However, despite following the rule of "there is no word that has the same meaning (tarāduf) in the Quran" as commonly known in the theory of iʻjāz al-qur’ān (the inimitability of the Qurʼān), her thoughts on tarāduf and their implications for the istinbāṭ (inference) of Islamic law are still unclear. Hence, this article discusses the relation and influence of ʻĀʼisha Bint al-Shāṭiʼs thoughts related to verses of laws. By studying the book of al-I’jāz al-Bayānī lil Qur`ān wa Masā’il Ibn al-Azraq and other relevance sources, this article concludes that ʻĀʼisha Bint al-Shāṭiʼs thoughts related to verses of law are still abstract and difficult to be applied, hence it does not give a significant influence on the strengthening of Islamic legal propositions.